COMMON FIXED POINT THEOREM FOR OCCASIONALLY WEAKLY COMPATIBLE MAPPINGS IN FUZZY METRIC SPACE - Jain, Suman; Jauhari, Nitin (Innovare Journal of Education, 2013)
The present paper deals with common fixed point theorem in fuzzy metric space by employing the notion of occasionally weakly compatible mappings. Our result generalizes the recent result of Singh et. al. [16]. Keywords : Common fixed points, fuzzy metric space, compatible maps, occasionally weakly compatible mappings and weak compatible mappings.Â 